Pengaruh suhu berbeda terhadap aktifitas enzim kolagenase dari usus ikan cunang (Congresox talabon) - Edison Edison; Andarini Diharmi; Mirna Ilza; Rahman Karnila; Febrina Tumangger (AGROINTEK, 2024)
Collagenase enzyme is a type of protease enzyme. The activity of an enzyme is affected by substrate, temperature, inhibitor, and pH.  One of the sources of enzymes is the internal organs of fish, namely the gut. This study aims to determine the activity of the collagenase enzyme at different temperatures. The experimental design used was randomized and full non-factorial. The treatments used were different incubation temperatures (50, 55, and 60oC) with three replications. Parameter analysis comprised fish proportion, enzyme activity, and dissolved protein. The results showed that the parts of the yellow pike conger fish were meat (64.25%), bones (19.98%), internal organs (including intestines) (4.50%), and skin (6.30%). Collagenase enzyme activity at temperatures 50, 55, and 60oC was 1.154, 1.702, and 0.667 U/mL, respectively. The dissolved proteins content was 12.89 mg/mL. The optimum temperature of the collagenase enzyme from the fish gut was 55oC with an enzyme activity of 1,702 U/mL. The dissolved protein content of the gut yellow pike conger extract was 12.89 mg/mL  Purification of the collagenase enzyme from of the gut yellow pike conger was needed to obtain a higher enzyme activity value.